Disturbance of thermal homeostasis following dynamic exercise - Kenny, G. P.; Jay, O.; Journeay, W. S. (Applied Physiology, Nutrition, and Metabolism, 2007)
Recovery from dynamic exercise results in significant perturbations of thermoregulatory control. These perturbations evoke a prolonged elevation in core body temperature and a concomitant decrease in sweating, skin blood flow, and skin temperature to pre-exercise baseline values within the early stages of recovery. Cutaneous vasodilation and sweating are critical responses necessary for effective thermoregulation during heat stress in humans. The ability to modulate the rate of heat loss through adjustments in vasomotor and sudomotor activity is a fundamental mechanism of thermoregulatory homeostasis. There is a growing body of evidence in support of a possible relationship between hemodynamic changes postexercise and heat loss responses. Specifically, nonthermoregulatory factors, such as baroreceptors, associated with hemodynamic changes, influence the regulation of core body temperature during exercise recovery. The following review will examine the etiology of the post-exercise disturbance in thermal homeostasis and evaluate possible thermal and nonthermal factors associated with a prolonged hyperthermic state following exercise.